NEW HOST RECORD OF ALTERNARIA BRASSICICOLA INFECTING TRIANGLE PALM (DYPSIS DECARYI) IN PAKISTAN - A. Javaid; N. Akhtar; A. Khan; A. Shoaib; R. Hafeez (Journal of Animal and Plant Sciences, 2016)
Triangle palm [Dypsis decaryi (Jum.) Beentje & Dansf.] is an important ornamental plant in many palm gardens of the world. Recently, a leaf spot disease on triangle palm was observed in Jinnah Garden, Lahore, Pakistan. Alternaria brassicicola (Schwein.) Wiltshire was isolated, purified and identified on the basis of morphological observations, analysing the Internal Transcribe Spacer (ITS) nucleotide sequence and phylogeny. Pathogenecity testing of the causal organism fulfilled the Koch’s postulates. To our knowledge, this is the first leaf spot disease report of triangle palm by A. brassicicola from Pakistan that needs attention for its proper control.
Keywords: Fungal pathogen; Internal Transcribe Spacer sequence; Morphology; Triangle palm